Translocation of insulin receptors into plasma membrane microdomains in response to insulin and to insulin-enhancing vanadium and chromium compounds - Al-Qatati, Abeer S. A., author; Roess, Deborah, advisor; Crans, Debbie, committee member; Graham, James, committee member; Anthony, Russ, committee member (Colorado State University. Libraries, 2010)
We have examined the translocation of insulin receptors into specialized, cholesterol-enriched membrane microdomains called lipid rafts following treatment of RBL-2H3 cells with insulin, bis-maltolatooxovanadium (BMOV) and tris(pyridinecarbxylato) chromium(III) (Cr(pic)3). Isopycnic sucrose gradient ultracentrifugation was used to subfractionate membrane fragments and insulin receptors were identified within low or high buoyant density membrane fractions using insulin receptor-specific antibodies and western blotting. Single particle tracking methods were used to confirm the confinement of individual insulin receptors within small membrane compartments on intact, viable RBL-2H3 cells. We demonstrated that insulin receptors translocate into lipid rafts upon binding insulin or following exposure to BMOV or Cr(pic)3 Phosphorylated insulin receptors also appeared in membrane raft fragments in response to insulin and/or insulin-mimicking compounds. Extraction of cholesterol from lipid rafts disrupted these microdomains and caused a decrease in the number of unphosphorylated and phosphorylated insulin receptors within these compartments. In addition to their ability to induce translocation of insulin receptors into lipid rafts, BMOV and Cr(pic)3 caused an increase in the number of phosphorylated IRS-1 molecules within these membrane fragments. To determine why Cr(pic)3 and BMOV might affect the distribution of insulin receptors in non-raft and raft compartments, membrane fluidity was evaluated in Cr(pic)3 and BMOV treated cells. Fluidity, as suggested by a decrease in lipid packing, was increased following treating 2H3 cells with either BMOV or Cr(pic)3 These results suggest that changes in lipid packing resulting from exposure of cells to either Cr(pic)3 and BMOV may affect the distribution of receptors in non-raft and raft compartments. Increased receptor localization in rafts or small membrane compartments evaluated by single particle tracking studies, would result in increased likelihood of insulin receptor phosphorylation within these signaling platforms. Thus rafts may be an important membrane structures involved in cell signaling events mediated by insulin receptors.
Covers not scanned.
Keywords: Insulin -- Receptors; Cell membranes; Vanadium -- Physiological effect; Chromium -- Physiological effect